Perancangan Sistem Pengendali Suhu dan Kelembaban untuk Budidaya Jamur Kuping - Felix Agni Gunawan; Irwan Iftadi; Wachid Ahmad Jauhari (Performa: Media Ilmiah Teknik Industri, 2013)
Mushroom cultivation is a new source of food. The cultivation requires the control of temperatureand humidity to produce good quality of mushroom. Nowdays, there are many tools of automatic or manual temperature and humidity control system. However, they have many limitation in practical situation, such as difficulties in use and assembly. This research aims to design and make a better prototype of temperature and humidity control system, which can improve the productivity of mushroom harvest.The research method has two phases, that are conceptual design and tool and system design. The conceptual design phase includes need identification, system design, and component selection. The second phase are tools application and main system, includes microcontroller, sensor, heater, refrigerator, electronic circuit, hardware, the programming tool, and assembly of tools.The research produces a prototype of temperature and humidity control by using ATmega16 microcontroller, which increases the response time of temperature and humidity control, automatically controlling the system, easy to use and maintanance, and improve the previous system which is still manual control. The prototype is able to help the farmers to control the temperature and humidity in mushroom cultivation. The result from the application of the prototype indicates that it can increase the productivity of the mushroom harvest.